Roles of the calcified cartilage layer and its tissue engineering reconstruction in osteoarthritis treatment - Wang, Weiyang; Ye, Ruixi; Xie, Wenqing; Zhang, Yueyao; An, Senbo; Li, Yusheng; Zhou, Yang (Frontiers in Bioengineering and Biotechnology, 2022)
Sandwiched between articular cartilage and subchondral bone, the calcified cartilage layer (CCL) takes on both biomechanical and biochemical functions in joint development and ordinary activities. The formation of CCL is not only unique in articular cartilage but can also be found in the chondro-osseous junction adjacent to the growth plate during adolescence. The formation of CCL is an active process under both cellular regulation and intercellular communication. Abnormal alterations of CCL can be indications of degenerative diseases including osteoarthritis. Owing to the limited self-repair capability of articular cartilage and core status of CCL in microenvironment maintenance, tissue engineering reconstruction of CCL in damaged cartilage can be of great significance. This review focuses on possible tissue engineering reconstruction methods targeting CCL for further OA treatment.